2015
DOI: 10.1371/journal.ppat.1005142
|View full text |Cite
|
Sign up to set email alerts
|

The Depsipeptide Romidepsin Reverses HIV-1 Latency In Vivo

Abstract: Pharmacologically-induced activation of replication competent proviruses from latency in the presence of antiretroviral treatment (ART) has been proposed as a step towards curing HIV-1 infection. However, until now, approaches to reverse HIV-1 latency in humans have yielded mixed results. Here, we report a proof-of-concept phase Ib/IIa trial where 6 aviremic HIV-1 infected adults received intravenous 5 mg/m2 romidepsin (Celgene) once weekly for 3 weeks while maintaining ART. Lymphocyte histone H3 acetylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
443
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 468 publications
(476 citation statements)
references
References 47 publications
20
443
5
Order By: Relevance
“…Although all investigated LRAs showed increased virus transcription, no changes in the latent-reservoir size were detected after the use of LRA in vivo (14,(18)(19)(20) or in vitro (24). One reason could be the short time during which LRAs were given to ART patients (ranging from 8 weeks for panobinostat to 3 weeks for romidepsin and 3 days for disulfiram), making the detection of reservoir decay problematic.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although all investigated LRAs showed increased virus transcription, no changes in the latent-reservoir size were detected after the use of LRA in vivo (14,(18)(19)(20) or in vitro (24). One reason could be the short time during which LRAs were given to ART patients (ranging from 8 weeks for panobinostat to 3 weeks for romidepsin and 3 days for disulfiram), making the detection of reservoir decay problematic.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in plasma HIV RNA was seen with panobinostat (19), romidepsin (20), and disulfiram (14), although in the panobinostat trial (19) this was demonstrated by a nonquantitative assay. Changes in HIV transcription have been demonstrated in all trials by showing an increase in the level of cell-associated HIV RNA (CA RNA) in total and resting CD4 ϩ T cells (21).…”
mentioning
confidence: 93%
See 3 more Smart Citations